If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 7 + 14b + -25b Combine like terms: 14b + -25b = -11b 18 = 7 + -11b Solving 18 = 7 + -11b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '11b' to each side of the equation. 18 + 11b = 7 + -11b + 11b Combine like terms: -11b + 11b = 0 18 + 11b = 7 + 0 18 + 11b = 7 Add '-18' to each side of the equation. 18 + -18 + 11b = 7 + -18 Combine like terms: 18 + -18 = 0 0 + 11b = 7 + -18 11b = 7 + -18 Combine like terms: 7 + -18 = -11 11b = -11 Divide each side by '11'. b = -1 Simplifying b = -1
| 4-22x+10=4(5-6x) | | 3x-9-10x-2=4(x+7) | | (10/3)/2 | | r^3+r^2-r-1=0 | | 5y+2w= | | 9(5k-3)= | | -8u-6=-6u+6 | | 2l+4/3l | | 5+16n=5 | | 2x-6x-3=0 | | 6.2x+1=5.2x | | 2+3*16+1=85 | | 2.5=3.5x | | 64/(15-7)*2-9 | | -4-8(6z+4)=8(4z-7)-1 | | 7r=-1/2 | | f(2+a)=5(2+a)-7 | | h+19/19=2 | | 3=-7 | | 950+700+4x=850+200+9x | | f(4)=5(4)-7 | | +5=1+k | | 11-4x=0.5 | | 19+-5p=-1 | | (3/5)w-(1/7)=(-3/7)w+(3/7) | | 7r=-7 | | 12-(1/26)(2x)=6-(1/26)(x) | | 7x*8k=8x-17k | | 5x+2/7x-6 | | 4y^2-5y^2+7y^2= | | [SQRT(x+3)]=2[SQRT(x)] | | x^3+2x^2-6x=12 |